Resistivity Properties of Limestone Rocks in Parts of Iraqi Kurdistan Region-NE Iraq - Aziz, Bakhtiar K.; Baban, Ezzaden N. (Sulaimani Journal for Pure and Applied Sciences, 2005)
To evaluate limestone rocks from the hydrogeological point of view and indicating optimum resistivities for dry and wet conditions an electrical resistivity ,study was performed in 34 locations surrounding Sulaimani, Kirkuk and Arbil cities. About 181 VES points were conducted using Shlumberger configuration. The authors selected six geological formations composed of limestone rock ibr this purpose.The field data u,as interpreted manually Using Ebert method and by the aid of computer using IPI2rvin anci Resixplus software. The optimum ranges of resistivity magnitudes have been determined for these geological formations in both wet condition (Forming aquifers) and dry condition (forming aquicludes). Among the studied formations Pila Spi. Sinjar and Aqra are appearing to be most suitable for making aquifers, While Kometan. Balambo and Qamchuqa Formations are frequently aquicludes.
Keywords: Resistivity prospectingGroundwater,carbonate rocks,